2006
DOI: 10.1099/jmm.0.46611-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial killing in gastric juice – effect of pH and pepsin on Escherichia coli and Helicobacter pylori

Abstract: The susceptibility of Escherichia coli and Helicobacter pylori to pH and the effect of pepsinmediated proteolysis were investigated. This was to establish the relative importance of their bacterial killing properties in gastric juice. Solutions in the pH range 1?5-7?4 with or without pig pepsin A were used, together with seven gastric juice samples obtained from patients undergoing routine gastric collection. Escherichia coli C690 (a capsulate strain), E. coli K-12 (a rough mutant) and Helicobacter pylori E5 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 17 publications
5
82
0
1
Order By: Relevance
“…For example, during a meal, gastric pH increases to an average value of 5.0 in humans (13). In addition, the ingested food constituents may provide protection for phage against extreme pH values, which has been demonstrated in a study involving bacteria (49). O'Flynn et al (34) have previously reported that phage Felix O1 can survive exposure to gastric contents directly collected from porcine stomachs at pH 2.5 for up to 2 h; this disagreement is presumably due to the difference in assay medium used.…”
Section: Discussionmentioning
confidence: 94%
“…For example, during a meal, gastric pH increases to an average value of 5.0 in humans (13). In addition, the ingested food constituents may provide protection for phage against extreme pH values, which has been demonstrated in a study involving bacteria (49). O'Flynn et al (34) have previously reported that phage Felix O1 can survive exposure to gastric contents directly collected from porcine stomachs at pH 2.5 for up to 2 h; this disagreement is presumably due to the difference in assay medium used.…”
Section: Discussionmentioning
confidence: 94%
“…pylori [26]. PLGA brought the pH in the same range during incubation, which explains the CFU decline.…”
Section: Bacteria Culture and Viabilitymentioning
confidence: 91%
“…However, even if counterproductive in the orthopaedic field, one might think of the pH drop induced by PLGA as an antimicrobial tool useful in dentistry, especially, as this biomaterial design would function according to the same principle as the barrier put up by the stomach, which is known to be an effective obstacle for harmful bacteria [26].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, nitrite diffusing into an acidified compartment generates another round of bactericidal RNI (53). The phagosomal milieu in the activated macrophage thus resembles to some degree the intragastric environment, whose microbicidal efficiency depends on the combined action of acid and RNI (10,60,106). In addition, like many other elements of the innate immune response, phagosomal acid serves to link the innate and adaptive immune systems.…”
Section: Acid As a Host Defensementioning
confidence: 99%